REVIEW : MIKROBA PENDEGRADASI LIGNOSELULOSA DARI TANAH GAMBUT - Arni Supriyanti; Sumardi Sumardi (Agros Journal of Agriculture Science, 2023)
Peatlands in Indonesia reach 22.5 million hectares, making Indonesia one of the five countries with the largest peatlands in the world. North Sumatra is one of 10 provinces with around 600,000 hectares of peat land. Despite having great peatland potential, this area is still considered of low value due to its unique geological and environmental specifications. Peat soils tend to be brittle and unequal, with a relatively high moisture content and little vegetation. Most of the peat soil contains 95% organic fraction and only 5% inorganic fraction. The organic fraction consists of 10-20% organic compounds, such as humic acid, himatemalonate, and humin. Meanwhile, most of the organic compounds consist of lignin, cellulose, hemicellulose, protein, suberin, waxes, tannins, resins, and others. The content of peat in Sumatra and Kalimantan is mostly wood, while the organic matter component is mostly composed of lignin which accounts for more than 60% dry matter. The content of other ingredients such as cellulose, hemicellulose, and protein generally does not exceed 11%. Lignocellulosic materials can be broken down into simple compounds by enzymes such as laccase and cellulase. These enzymes are extracellular enzymes produced by bacteria, fungi or molds, and plants, which are released into the soil system. An important role of this enzyme is the mineralization of nutrients and the decomposition of organic matterKeywords : Peat Soil, Lignocellulose, Fungi, bacteria INTISARI            Lahan gambut di Indonesia mencapai 22,5 juta hektar, sehingga Indonesia termasuk salah satu dari lima negara dengan lahan gambut terluas di dunia. Sumatera Utara merupakan salah satu dari 10 provinsi dengan sekitar 600.000 hektar lahan gambut. Meskipun memiliki potensi lahan gambut yang besar, kawasan ini masih dianggap bernilai rendah karena spesifikasi geologis dan lingkungannya yang unik. Tanah gambut cenderung rapuh dan tidak ekuivalen, dengan kadar air yang relatif tinggi dan vegetasi sedikit. Kandungan tanah gambut Sebagian besar mengandung fraksi organik 95% dan hanya 5% fraksi anorganik. Fraksi organik terdiri dari senyawa organic sebesar 10-20%, seperti asam humat, himatemalonat, dan humin. Sementara itu, sebagian besar senyawa organik terdiri dari lignin, selulosa, hemiselulosa, protein, suberin, lilin, tanin, resin, dan lainnya. Kandungan bahan gambut di Sumatera dan Kalimantan sebagian besar berupa bahan kayu, sedangkan komponen bahan organiknya sebagian besar tersusun atas lignin yang jumlahnya lebih dari 60% bahan kering. Kandungan bahan lain seperti selulosa, hemiselulosa, dan protein umumnya tidak melebihi 11%. Bahan lignoselulosa dapat dipecah menjadi senyawa sederhana oleh enzim seperti lakase dan selulase. Enzim-enzim tersebut merupakan enzim ekstraseluler yang dihasilkan oleh bakteri, cendawan atau cendawan, dan tumbuhan, yang dilepaskan ke dalam sistem tanah. Peran penting enzim ini adalah mineralisasi nutrisi dan dekomposisi bahan organik. Kata kunci : Tanah Gambut, Lignoselulosa, Fungi, bakteri